Current Management of Pleuropulmonary Blastoma: A Surgical Perspective - Samantha Knight; Tristan Knight; Amir Khan; Andrew J. Murphy (MDPI AG, 2019)
Pleuropulmonary blastomas (PPB) are pediatric, embryonal cancers of the lung parenchyma and pleural surfaces and are among the most common DICER1—related disorders. These tumors undergo evolution through several forms, allowing division into types I, Ir, II, and III, with correlates to the age of diagnosis and prognosis. We sought to provide a comprehensive review of the relevant literature describing the characteristics of these tumors and their multidisciplinary treatment, with an emphasis on surgical management. We describe the complementary roles of chemotherapy and surgery in the successful management of this disease. We discuss the timing of surgery and options for surgical approaches. We address the differentiation of PPB from congenital pulmonary airway malformation and the role of DICER1 testing for children with pulmonary cysts.